DIALEKTIKA KONSEPTUAL DAN PENERAPAN ASBĀB AL-NUZŪL - Fauzi, Mhd. Abyan (LP2M Universitas PTIQ Jakarta, 2023)
This paper is the result of research that aims to re-examine the understanding of the concept of asbāb al-nuzūl contained in various ‘ulūm al-Qur`an literature. This research is a library research by examining a number of written documents such as journals, books, articles, and other writings related to asbāb al-nuzūl. After that, descriptive-analytic techniques were used to analyze the data sources. The results of this study found that classical and contemporary scholars have different understanding of the text of the Qur'an which has implications for differences in formulating the method of ‘ulūm al-Qur`an, one of which is asbāb al-nuzūl. For classical scholars, asbāb al-nuzūl is only understood as an explanation of the verses that were revealed or even only used to interpret certain verses. Meanwhile, contemporary scholars understand asbāb al-nuzūl not only to assist commentator in interpreting verses, but also as a method for finding the deepest meaning of the verses revealed so that they remain relevant at all times in any situation and condition